2010
DOI: 10.1152/japplphysiol.00281.2010
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training improves skeletal muscle function and Ca2+ handling-related protein expression in sympathetic hyperactivity-induced heart failure

Abstract: The cellular mechanisms of positive effects associated with aerobic exercise training on overall intrinsic skeletal muscle changes in heart failure (HF) remain unclear. We investigated potential Ca2+ abnormalities in skeletal muscles comprising different fiber compositions and investigated whether aerobic exercise training would improve muscle function in a genetic model of sympathetic hyperactivity-induced HF. A cohort of male 5-mo-old wild-type (WT) and congenic alpha2A/alpha2C adrenoceptor knockout (ARKO) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 33 publications
5
49
0
9
Order By: Relevance
“…This ultimately leads to improved skeletal muscle function (23). Regarding skeletal muscle atrophy, even aerobic exercise training is able to re-establish soleus and plantaris trophicity in our sympathetic hyperactivityinduced HF mouse model (22,23). This is somewhat surprising since resistance and not aerobic exercise training swings the protein synthesis/degradation balance in favor of protein synthesis.…”
Section: Impact Of Exercise Training On Skeletal Muscle Myopathymentioning
confidence: 90%
See 4 more Smart Citations
“…This ultimately leads to improved skeletal muscle function (23). Regarding skeletal muscle atrophy, even aerobic exercise training is able to re-establish soleus and plantaris trophicity in our sympathetic hyperactivityinduced HF mouse model (22,23). This is somewhat surprising since resistance and not aerobic exercise training swings the protein synthesis/degradation balance in favor of protein synthesis.…”
Section: Impact Of Exercise Training On Skeletal Muscle Myopathymentioning
confidence: 90%
“…Interestingly, we have demonstrated that aerobic exercise training improves the net balance of skeletal muscle Ca 2+ -handling proteins in mice (60). Moreover, exercise training restores the expression levels of proteins involved in sarcoplasmic Ca 2+ release and reuptake in soleus and plantaris muscles from HF mice (23). This ultimately leads to improved skeletal muscle function (23).…”
Section: Impact Of Exercise Training On Skeletal Muscle Myopathymentioning
confidence: 91%
See 3 more Smart Citations